Hidden damage and current needs: pulpit and pew in Lutheran Australia - Koepping, Elizabeth (Scottish journal of theology, 2007)
In both world wars, Lutherans of German origin in Australia were used as scapegoats by the government, as that church and its people were regarded as German and therefore a safely bounded object for spite. South Australia, the heartland of Lutheranism, was especially attacked, some pastors and long-settled citizens being interned, restricted and otherwise rejected: actual worship was also affected. The traumatic effects have lasted until now in rural communities such as ‘Hope’, the subject of long-term anthropological research by the writer. These effects are not merely personal, which are grim enough, but inevitably, in deeply religious communities with limited sacred–secular split, also theological. However, given the understandable yet unacceptable unwillingness of the church to face the past, the consequences are ignored. This article argues that crises, whether natural, the result of war, or of wrong behaviour by church officers, are present in every church context through the past to the contemporary world, as is the tendency to ignore the impact in favour of maintaining the institution. The lasting theological effects on laity and clergy should be acknowledged and acted upon in training and ministry for many years after the events, whether they resulted from the behaviour of one person in a parish or an entire government or empire. This may mean accepting the implications of locality for lived theology.